Numerical analysis of effects of crosswind and turbulence intensity on aircraft wake-vortex in ground proximity - Sindhu Paramasivam (2015)
Aircraft wake vortices are major problems in many busy airports. In this thesis, such wake vortices in ground proximity are simulated using a set of in-house CFD codes for solving Navier-Stokes equations numerically using Large-eddy simulation. The simulations are performed with flat ground for different crosswind velocities and turbulence intensities. The parameters like circulation, lateral and vertical position of the vortex centre, radius of the core, vortex separation distance are investigated with the aid of necessary graphs. Lamb-Oseen vortex model is used to initiate the counter-rotating vortex pair in the computational domain. The vortex is initialised at a time step when the crosswind flow has reached the end of the domain so that the impact of background turbulence due to the crosswind is replicated. Crosswinds with low velocities are not sufficient enough to accelerate the decay and push the vortex out of the domain while a crosswind flow with higher velocities can initiate the vortex decay at earlier time and is capable of pushing the downwind vortex out of the domain. The plot of a~' versus velocity for downwind vortex at early times .varies linearly with a non-zero y-intercept while that of upwind vortex at later times can be approximated to a linear curve with slight deviations in low velocity regime. Vortex pair descents initially and then bounces back for all crosswind velocities. The bounce back is height is lesser for higher velocities of crosswind. The separation distance between the vortices is maintained same for all crosswind velocities at earlier times. Low turbulence intensities do not affect any of the vortex characteristics while higher turbulence intensities have slight effects on the large-scale turbulent structures formed. The effects of crosswind and turbulence intensity in the formation of secondary vortices and its interaction with the primary vortices are described in detail.